Apuntes sobre la causal de anulación de laudos por materia no arbitrable, y su invocación de oficio - Arrarte Arisnabarreta, Ana María (Pontificia Universidad Católica del Perú, 2015)
This paper analyzes mainly the figure of the annulment of an arbitratien award for having ruled on a non-arbitrable matters and the power of judges to invoke this ground of trade. With that purpose , this paper also consider some important legal concepts as the nullity, the arbitrability and public order as well as the Peruvian Arbitration Act and the grounds for annulment of awards which is expected.

El presente artículo analiza, principalmente, la figura de la anulación de un laudo por haberse pronunciado sobre una materia no arbitrable y la potestad de los jueces de invocar esta causal de oficio. Con ese fin, estudia también algunos conceptos jurídicos importantes como la nulidad, la arbitralidad y el orden público, así como también a la Ley de Arbitraje peruana y las causales de anulación de Laudos que esta prevé.
Notes on the ground for annulment of awards not arbitrable matter, and its invocation of trade
Keywords: Arbitration Award; Annulment; Arbitralidad; Peruvian Arbitration Law; Laudo; Anulación; Arbitralidad; Ley de Arbitraje Peruana; https://purl.org/pe-repo/ocde/ford#5.05.00